Redefinition of International Peace in the Use of Outer Space Based on Peacefull Purpose Principle in Outer Space Treaty 1967 - Tandungan, Edmondus Sadesto; Salim, Andre; Christy, Gracesy Prisela (UNISSULA, 2025)
The 1967 Outer Space Treaty was established as a basis for the peaceful exploration and use of outer space. However, since its inception, there has been no standard definition of the phrase